The paradox of Polish social assistance - Chaczko, Krzysztof (Research Papers of Wrocław University of Economics, 2018)
The Polish social assistance system, designed on the eve of systemic transformation, has had a major role in mitigating the effects of economic and social change. And in this sense, it served as a social welfare, despite the nomenclature in the form of social assistance. The purpose of this article is to examine whether, after almost three decades of operation, the system is still closer to what can be called social care or can it, in line with the terminology adopted, focus on aid. In attempt to answer these questions, the terms ‘social care’ and ‘social assistance’ were first defined to distinguish between the legal forms of care and aid services. Then, using quantitative data on the benefits provided in social assistance, it was concluded that care services are still prevalent in social assistance, which leads to a terminological-functional paradox
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2018, Nr 510, s. 9-17
Keywords: social care; social assistance; social assistance benefits; opieka społeczna; pomoc społeczna; świadczenia w pomocy społecznej